The Impacts of Monetary Policy Announcements and Derivatives Maturity on the Mexican Peso Exchange Rate Volatility: GARCH and OCHL Range Models - Magnolia Miriam Sosa Castro; Maria Alejandra Cabello Rosales; Edgar Ortiz Calisto (Lecturas de Economía)
We analyze the impact of interest rate changes and derivatives maturity announcements on exchange rate volatility in Mexico. To do so, we first estimate volatility using four measures of range volatility (OCLH models) and three extensions of the GARCH family (GARCH, TARCH and EGARCH), assuming normal distribution, t-Student and GED. Once volatilities are estimated, the impact of monetary policy announcements and derivatives maturity on the MexDer is estimated using daily closing, opening, high, and low data during the period January/2013-April/2024. The results show that range volatility measures underestimate exchange rate volatility. Apparently, derivatives maturities and monetary policy announcements have a negative effect on range/intraday volatilities, but not on the conditional volatility that contemplates persistence and asymmetry in volatility.